Hematospermia in a returned traveler - Lang, Raynell; Minion, Jessica; Wong, Alexander (Canadian Urological Association Journal, 2017)
Hematospermia is a common complaint among patients seen in outpatient urology clinics. The differential diagnosis is broad and includes inflammatory, infectious, neoplastic, structural, systemic, and traumatic causes. The most common infectious causes are uropathogens and sexually transmitted infections. However, with increasing global travel, physicians must maintain a high clinical suspicion for pathogens not endemic to their region, including Echinococcus, Mycobacterium tuberculosis, and Schistosoma.1 We present a case of hematospermia in a traveler returning from Eastern Africa with exposure to Lake Malawi. The patient’s microscopic analysis of semen was positive for Schistosoma haematobium, revealing a rare presentation of S. haematobium infection.